Proton magnetic resonance spectroscopy in children with fetal alcohol spectrum disorders Espectroscopia por ressonância magnética de prótons em crianças com transtornos do espectro alcoólico fetal - Rita de Cássia Ferreira Gonçalves; Marcio Moacyr Vasconcelos; Letícia Oliveira Faleiros; Luiz Celso Hygino da Cruz Jr.; Romeu Cortes Domingues; Adriana Rocha Brito; Jairo Werner Jr.; Gesmar Volga Haddad Herdy (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To analyze the metabolic constitution of brain areas through proton magnetic resonance spectroscopy in children affected with fetal alcohol spectrum disorder compared with normal children. METHOD: The sample of this case-control study included eight boys with epidemiologic history of in utero exposure to alcohol (median age 13.6±3.8 years) who were diagnosed with fetal alcohol spectrum disorder, and eight controls (median age 12.1±3,4 years). An 8 cm³ single voxel approach was used, with echo time 30 ms, repetition time 1500 ms, and 128 acquisitions in a 1.5T scanner, and four brain areas were analyzed: anterior cingulate, left frontal lobe, left striatum, and left cerebellar hemisphere. Peaks and ratios of metabolites N-acetylaspartate, choline, creatine, and myo-inositol were measured. RESULTS: Children with fetal alcohol spectrum disorder showed a decrease in choline/creatine ratio (p=0.020) in left striatum and an increase in myo-inositol/creatine ratio (p=0.048) in left cerebellum compared with controls. There was no statistically significant difference in all peaks and ratios from the anterior cingulate and frontal lobe between the two groups. CONCLUSION: This study found evidence that the left striatum and left cerebellum are affected by intrauterine exposure to alcohol. Additional studies with larger samples are necessary to expand our knowledge of the effects of fetal exposure to alcohol. OBJETIVO: Analisar a composição metabólica de áreas encefálicas através da espectroscopia de prótons por ressonância magnética em crianças com transtornos do espectro alcoólico fetal e crianças normais. MÉTODO: A amostra deste estudo de casos-controles incluiu 8 meninos com história epidemiológica de exposição fetal ao álcool (idade mediana 13,6±3,8 anos), diagnosticados com transtorno do espectro alcoólico fetal, e 8 controles (idade mediana 12,1±3,4 anos). Utilizou-se voxel único de 8 cm³, tempo de eco 30 ms, tempo de repetição 1.500 ms, 128 aquisições, em scanner de 1,5T para as seguintes áreas: cíngulo anterior, lobo frontal esquerdo, estriado esquerdo e hemisfério cerebelar esquerdo. Estudaram-se os picos e as razões dos metabólitos N-acetilaspartato, colina, creatina e o mio-inositol. RESULTADOS: As crianças acometidas apresentaram diminuição da razão colina/creatina (p=0,020) no estriado esquerdo, e aumento da razão mio-inositol/creatina (p=0,048) no cerebelo esquerdo. Não houve diferença estatisticamente significativa nos valores encontrados no cíngulo anterior e lobo frontal entre os dois grupos. CONCLUSÃO: Este estudo encontrou evidências de que o estriado e o cerebelo esquerdos são acometidos pela exposição intra-uterina ao álcool. Estudos adicionais com amostras maiores são essenciais para expandir nosso conhecimento dos efeitos da exposição fetal ao álcool.